The influence of social value on halal purchase decisions, trust, and halal awareness - Firmansyah, Firmansyah; Putri, Ira Widyana; Putri, Sri Septiani Kurnia (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This study aims to analyze the impact of emotional value, social value, and awareness on halal purchase decisions. A purposive sampling method was utilized, resulting in 113 respondents. The results indicate that emotional value positively and significantly influences halal purchase decisions, suggesting that consumers who attribute high emotional value to halal products are more inclined to buy them. Conversely, the study indicates that social value and trust do not significantly impact halal purchase decisions. While emotional value was significant, the lack of impact from social value and trust suggests a need for consumer education. Companies should invest in educating consumers about the benefits and quality of halal products, which may help build trust and awareness over time